DEMOGRAPHIC CHARACTERISTICS AND ABO BLOOD GROUP GENOTYPES DISTRIBUTION AMONG SICKLE CELL ANEMIA PATIENTS IN BIRNIN KEBBI, NORTHWESTERN NIGERIA - Tajudeen Olanrewaju Yahaya; Asiya Koko Attahiru; Abdulgafar Bala Ibrahim; Mutiyat Kehinde Adewale; Adamu Zainab Fari; Abdullahi Saadatu (Majalah Biomorfologi, 2024)
Highlights Sickle cell anemia affects both males and females in Birnin Kebbi and is predominant among children between 1 to 10 years of age. It is also more prevalent but less severe among individuals with O- and A+ ABO blood groups in the city.   Abstract Background: Demographic information and ABO blood group genotypes have been shown by studies to be useful tools in the management of sickle cell anemia. Regrettably, there is a dearth of literature on this information in Birnin Kebbi, northwestern Nigeria. Objective: This study determined demographic characteristics, ABO blood group genotypes, and sickle cell genotypes of sickle cell anemia patients in Birnin Kebbi. Material and Method: A structured checklist was used to collect data from the medical records of 99 patients who attended the Federal Medical Center in the city between November 2022 to November 2023. Result: The results revealed that most of the patients fell within the 1 to 10 years age group, comprising 44 individuals (44.4%), and the 11 to 20 years age group, comprising 33 individuals (33.3%). Of the patients, 48 (48.5%) were males, while 51 (51.5%) were females. Patients with ABO blood genotype O- (33.3%) and A+ (18.0%) were the most prevalent and least severely affected, while blood groups O+ (3%) and AB- (6%) were the least prevalent and most severely affected. Two variants of sickle cells (HbSS and HbSC) were identified, with HbSS (92.9%) being the most prevalent. Conclusion: Based on these findings, efforts should be made to ensure an ample blood supply with groups O-, A, and AB+ in blood banks. Moreover, studies have shown ABO blood groups to influence responses to diets, so precision medicine tailored to individual patients' blood groups is recommended. Individuals with O+ and AB- -blood groups should be given special attention, as they exhibit the severe form of the disease.